Potential plasmid-curing agent, 8-epidiosbulbin E acetate, from dioscorea bulbifera L. against multidrug-resistant bacteria - Shriram, Varsha; Jahagirdar, Sheetal S.; Latha, C.; Kumar, Vinay; Puranik, Vedavati G.; Rojatkar, Supada; Dhakephalkar, Prashant K.; Shitole, M. G. (International Journal of Antimicrobial Agents, 2008)
Bioassay-guided fractionation of an aqueous methanolic extract of Dioscorea bulbifera L. bulbs was performed using organic solvents. A novel plasmid-curing compound was identified as 8-epidiosbulbin E acetate (EEA) (norditerpene) on the basis of modern spectroscopic analysis and X-ray crystallography. EEA exhibited broad-spectrum plasmid-curing activity against multidrug-resistant (MDR) bacteria, including vancomycin-resistant enterococci. EEA cured antibiotic resistance plasmids (R-plasmids) from clinical isolates of Enterococcus faecalis, Escherichia coli, Shigella sonnei and Pseudomonas aeruginosa with 12-48% curing efficiency. The reference plasmids of Bacillus subtilis (pUB110), E. coli (RP4), P. aeruginosa (RIP64) and Salmonella typhi (R136) were cured with efficiency ranging from 16% to 64%. EEA-mediated R-plasmid curing decreased the minimal inhibitory concentration of antibiotics against MDR bacteria, thus making antibiotic treatment more effective. The antibiotic resistance pattern revealed that the compound was effective in the reversal of bacterial resistance to various antibiotics. In addition, the compound did not show any cytotoxicity against a broad range of human cancer cell lines, namely MCF-7 (breast cancer), SiHa (cervical cancer) and A431 (epidermal carcinoma), and hence has the potential to be used as a lead compound for drug discovery programmes. (C) 2008 Elsevier B. V. and the International Society of Chemotherapy. All rights reserved.
Keywords: 8-Epidiosbulbin E acetate; Antibiotic resistance; Dioscorea bulbifera; Plasmid curing

Antibacterial & antiplasmid activities of Helicteres isora L. - Shriram, Varsha; Jahagirdar, Sheetal S.; Latha, C.; Kumar, Vinay; Dhakephalkar, Prashant K.; Rojatkar, Supada; Shitole, Mahadeo G. (Indian Journal of Medical Research, 2010)
Background & objectives: The multiple drug resistance (MDR) is a serious health problem and major challenge to the global drug discovery programmes. Most of the genetic determinants that confer resistance to antibiotics are located on R-plasmids in bacteria. The present investigation was undertaken to investigate the ability of organic extract of the fruits of Helicteres isora to cure R-plasmids from certain clinical isolates. Methods: Active fractions demonstrating antibacterial and antiplasmid activities were isolated from the acetone extracts of shade dried fruits of H. isora by bioassay guided fractionation. Minimal inhibitory concentration (MIC) of antibiotics and organic extracts was determined by agar dilution method. Plasmid curing activity of organic fractions was determined by evaluating the ability of bacterial colonies (pre treated with organic fraction for 18 h) to grow in the presence of antibiotics. The physical loss of plasmid DNA in the cured derivatives was further confirmed by agarose gel electrophoresis. Results: The active fraction did not inhibit the growth of either the clinical isolates or the strains harbouring reference plasmids even at a concentration of 400 mu g/ml. However, the same fraction could cure plasmids from Enterococcus faecalis, Escherichia coli, Bacillus cereus and E. coli (RP4) at curing efficiencies of 14, 26, 22 and 2 per cent respectively. The active fraction mediated plasmid curing resulted in the subsequent loss of antibiotic resistance encoded in the plasmids as revealed by antibiotic resistance profile of cured strains. The physical loss of plasmid was also confirmed by agarose gel electrophoresis. Interpretation & conclusions: The active fraction of acetone extract of H. isora fruits cured R-plasmids from Gram-positive and Gram-negative clinical isolates as well as reference strains. Such plasmid loss reversed the multiple antibiotic resistance in cured derivatives making them sensitive to low concentrations of antibiotics. Acetone fractions of H. isora may be a source to develop antiplasmid agents of natural origin to contain the development and spread of plasmid borne multiple antibiotic resistance.
Keywords: antibacterial activity; Antibiotic resistance; antiplasmid activity; Helicteres isora; multiple drug resistance; plasmid-curing

Cytotoxic activity of 9,10-dihydro-2,5-dimethoxyphenanthrene-1,7-diol from Eulophia nuda against human cancer cells - Shriram, Varsha; Kumar, Vinay; Kishor, P. B. Kavi; Suryawanshi, Sharad B.; Upadhyay, Ankur K.; Bhat, Manoj K. (Journal of Ethnopharmacology, 2010)
Ethnopharmacological relevance: Eulophia nuda L. (Orchidaceae) is a medicinally important terrestrial orchid used for the treatment of tumours and various health problems by the local healers throughout the Western Ghats region in Maharashtra (India). Aim of the study: To isolate the active molecule from Eulophia nuda and to study its cytotoxic potential against human cancer cells. Materials and methods: The crude methanolic extract of Eulophia nuda tubers was fractionated by stepwise gradient of the solvents chloroform-methanol to isolate the pure compound. Isolated pure compound was assessed for its cytotoxic potential against human breast cancer cell lines, MCF-7 and MDA-MB-231 using MTT assay. Structure elucidation of the isolated active compound was carried out by extensive spectroscopic analysis including (1)H NMR, (13)C NMR, NOESY, COSY, LC-MS and IR. Results: The isolated active molecule was identified as phenanthrene derivative 9,10-dihydro-2,5-dimethoxyphenanthrene-1,7-diol. This compound showed good antiproliferative activity against human breast cancer cell lines MCF-7 (91%) and MDA-MB-231 (85%) at 1000 mu g/ml concentration. Conclusion: 9,10-Dihydro-2,5-dimethoxyphenanthrene-1,7-diol from Eulophia nuda tubers showed good growth suppressive effect against human cancer cell lines MCF-7 and MDA-MB-231 making it a potential biomolecule against human cancer. (C) 2009 Elsevier Ireland Ltd. All rights reserved.
Keywords: Cytotoxic activity; Eulophia nuda; Phenanthrene derivatives

Crucial role of ocean-atmosphere coupling on the Indian monsoon anomalous response during dipole events - Krishnan, R.; Sundaram, Suchithra; Swapna, P.; Kumar, Vinay; Ayantika, D. C.; Mujumdar, M. (Climate Dynamics, 2011)
This paper examines an issue concerning the simulation of anomalously wet Indian summer monsoons like 1994 which co-occurred with strong positive Indian Ocean Dipole (IOD) conditions in the tropical Indian Ocean. Contrary to observations it has been noticed that standalone atmospheric general circulation models (AGCM) forced with observed SST boundary condition, consistently depicted a decrease of the summer monsoon rainfall during 1994 over the Indian region. Given the ocean-atmosphere coupling during IOD events, we have examined whether the failure of standalone AGCM simulations in capturing wet Indian monsoons like 1994 can be remedied by including a simple form of coupling that allows the monsoon circulation to dynamically interact with the IOD anomalies. With this view, we have performed a suite of simulations by coupling an AGCM to a slab-ocean model with spatially varying mixed-layer-depth (MLD) specified from observations for the 1994 IOD; as well as four other cases (1983, 1997, 2006, 2007). The specification of spatially varying MLD from observations allows us to constrain the model to observed IOD conditions. It is seen that the inclusion of coupling significantly improves the large-scale circulation response by strengthening the monsoon cross-equatorial flow; leading to precipitation enhancement over the subcontinent and rainfall decrease over south-eastern tropical Indian Ocean-in a manner broadly consistent with observations. A plausible physical mechanism is suggested to explain the monsoonal response in the coupled frame-work. These results warrant the need for improved monsoon simulations with fully coupled models to be able to better capture the observed monsoon interannual variability.
Keywords: Anomalous wet Indian monsoons; Indian ocean dipole; Numerical simulation; Ocean-atmosphere coupling

Long-lived monsoon depressions of 2006 and their linkage with the Indian ocean Dipole - Krishnan, R.; Ayantika, D. C.; Kumar, Vinay; Pokhrel, Samir (International Journal of Climatology, 2011)
A highlight of the 2006 boreal summer monsoon season was the enhanced activity of long-lived monsoon depressions and low-pressure systems (LPS) over the Indian region. Another important phenomenon during this period was the evolution of a positive Indian Ocean Dipole (PIOD) event. Although previous studies have investigated the impact of PIOD on the large-scale monsoon response, their influence on monsoon LPS activity is not well understood. Based on detailed diagnostic analyses of monsoon LPS during 2006, as well as those associated with other PIOD events during 1958-2007, the present work addresses two specific issues concerning the roles of (a) PIOD-induced large-scale circulation changes and (b) internal feedbacks between latent heating and dynamics, in sustaining the monsoon LPS activity. The results show that PIOD conditions generally favour increased propensity of long-lived (>5 days) LPS with long westward tracks extending into northwest India. The average contribution of long-lived monsoon LPS to the total is found to be approximately 12% higher during PIOD episodes as compared to non-PIOD. The PIOD events showed two important large-scale elements conducive for enhancement of LPS activity: (a) strengthening of cross-equatorial moisture transport from south-eastern tropical Indian Ocean into the Bay of Bengal and (b) enrichment of barotropic instability of monsoon flow. Estimates of latent-heating profiles from TRMM-satellite products during the 2006 LPS showed heating in the mesoscale updrafts above 600 hPa with maximum approximately 400 hPa; while cooling prevailed in lower levels. Stratiform precipitation covered approximately 70-85% of rain area during the prolonged LPS; and the large-scale monsoon Hadley-type circulation was found to be intensified with strong mid-level inflows entering the stratiform rain region. The overall findings suggest that the PIOD-induced background circulation together with internal feedbacks between mesoscale convective systems and large-scale circulation can effectively enhance the longevity of monsoon LPS. These results should serve as important inputs for numerical weather forecasting of extreme rainfall events associated with the regional monsoon phenomenon. Copyright (C) 2010 Royal Meteorological Society
Keywords: Indian ocean dipole; life period; monsoon depressions

Phytochemical profile, anti-oxidant, anti-inflammatory, and anti-proliferative activities of Pogostemon deccanensis essential oils - Kumar, Vinay; Shriram, Varsha; Bhagat, Rani; Khare, Tushar; Kapse, Shivanjali; Kadoo, Narendra (3 Biotech, 2019)
Essential oils (EOs) obtained from aerial parts of Pogostemon deccanensis were analyzed for GC-MS profiling, and evaluated for antioxidant, anti-inflammatory, and anti-proliferative activities. GC-MS analysis revealed a total of 47 constituents, establishing the EOs rich in sesquiterpene with >20 sesquiterpenes constituting around 77% of the total EO yield. Major constituents included Curzerene (Benzofuran, 6-ethenyl-4,5,6,7-tetrahydro-3,6-dimethyl-5-isopropenyl-, trans-) (26.39%) and epi-Cadinol (22.68%), Ethanone, 1-(2,4,6-trihydroxyphenyl) (6.83%, Acetophenones), and Boldenone (3.47%, anabolic steroid). EOs found to be rich in phytochemicals attributed for antioxidant potentials of aromatic/medicinal plants, viz., flavonoids (2.71 mu g quercetin equivalents g(-1) EO), total phenols (3.94 mu g gallic acid equivalents (GAE) g(-1) EO), carotenoids (14.3 mu g -carotene equivalents g(-1) EO), and ascorbic acid (2.21 mu g ascorbic acid equivalents g(-1) EO). P. deccanensis EOs exhibited striking antioxidant activities assessed by wide range of assays including ferric reducing antioxidant potential (FRAP, 255.3 GAE at 2 mu g mL(-1) EO), total antioxidant activity (TAA, 264.3 GAE at 2 mu g ml(-1)) of EO, DPPH (65% inhibition at 2 mu g mL(-1)), and OH (58% inhibition at 2 mu g mL(-1)) scavenging. Interestingly, EOs showed considerably higher anti-lipid peroxidation activity than the standard antioxidant molecule ascorbic acid, with 50% protection by 1.29 mu g mL(-1) EO against 20.0 mu g mL(-1) standard. EOs showed strong anti-inflammatory activity with 50% inhibition at 1.95 mu g mL(-1) EO. The anti-proliferative activity of EOs was tested against mouse cancer cell line and the EOs proved a potent anti-proliferative agent with only 2.1% cell survival at 2 mu g mL(-1) EO, whereas the EOs were largely non-toxic-to-normal (non-cancerous) cells with approximately 80% cell survival at the 2 mu g mL(-1) EOs. This being the first attempt of phytochemical profiling and wide array of biological activities of P. deccanensis EOs holds significance as the striking activities were observed at very low concentrations, in some cases at lower than the commercial standards, and has, therefore, great potential for pharmaceutical or commercial exploration.
Keywords: Anti-inflammatory activity; Anti-proliferative activity; Antioxidants; Cytotoxicity; Essential oils